A STUDY OF ASSOCIATIVE MEANING FOUND IN THE NEWS ARTICLES ON REGIONAL ELECTIONS LAW IN THE JAKARTA GLOBE ONLINE NEWSPAPER - CHARMILA, WINDA AYU (Jurnal Ilmiah Mahasiswa FIB, 2015)
Charmila. Winda Ayu. 2015. A Study of Associative Meaning Found in the News Articles on Regional Election Law in The Jakarta Globe Online Newspaper. Study Program of English, Universitas Brawijaya. Supervisor: Istiqomah Wulandari. ; Co-Supervisor: Muhammad Rozin. Keywords: Associative meaning, news, regional, election, The Jakarta Globe. Language is used as a communication tool to express someone’s idea and opinion. In delivering the idea or opinion either through spoken or written, there should be meaning behind the words or sentence that is uttered. This research focused on the interpretation of associative meaning in the news article of regional election law in The Jakarta Globe using Leech’s theory (1983). The Jakarta Globe is an Indonesian newspaper that uses English as the language to write its news articles. There are two problems in this study, those are (1) What types of associative meaning used in the articles about regional election law in The Jakarta Globe (2) What are the interpretations of associative meaning found in the articles about regional election law in The Jakarta Globe. This study used qualitative approach in analyzing the associative meaning. Document analysis is also used here because the data in this study are taken from news article in a form of written text. The result of this study showed that there are fifty five sentences containing associative meaning. The associative meaning was found in word, phrase, and also sentence. There are twenty five words belonging to reflected meaning, thirty words of stylistic meaning, twelve words of connotative meaning, two words of collocative meaning, and twenty one sentences of affective meaning. Stylistic meaning is the type of meaning that is the most commonly found from the data of this study. It can be caused by the news article about regional election law used many terms that is related with law and formal words. The writer suggests the next researcher to conduct a research associative meaning or the whole types of meaning from Leech with different object such as novel, movie, songs, and so on. The writer also suggests the next researcher to use different theory in analyzing meaning.